DIRECTION-ASYMMETRIC EQUIVALENCE IN LEGAL TRANSLATION - DUBĚDA, Tomáš (Comparative Legilinguistics, 2021)
The concept of equivalence, despite the criticism it has received in the past decades, remains a useful framework for the study of correspondence between legal terms. In the present article, I address the question of direction-asymmetric equivalence in legal translation, i.e. equivalence that does not obey the “one-to-one” principle, and which usually implies that the translator’s decision-making is more difficult in one direction than in the other. This asymmetry may be triggered by intrinsic semantic characteristics of legal terms (synonymy and polysemy), by differences between legal systems (system-specific terms, the procedures used for their translation and their handling in lexicographic sources, competing legal systems, tension between cultural boundedness and neutrality), or by social factors (L1 vs. L2 translation). The instances of directional asymmetry discussed are illustrated with examples from French and Czech.